Bacteriostatic or bactericidal? Impedometric measurements to test the antimicrobial activity of Arthrospira platensis extract. (December 2020) - Bancalari, Elena; Martelli, Francesco; Bernini, Valentina; Neviani, Erasmo; Gatti, Monica
Abstract: In recent years, increasing consumer's demand for even cleaner label, functional, safe and high quality products has led to searching for new antimicrobial agents of natural origin that can improve quality and safety with reducing the impact on the product composition. In this scenario the use of algae extracts in food formulations as antimicrobial agents is taking more and more interest. In particular, the antimicrobial potential of Arthrospira platensis has already been tested in vitro, using the agar well diffusion method or the broth dilution method, that can provide a quantitative estimation of minimum inhibitory concentration (MIC). Even if several methods are already in use to test the MIC and minimum bactericidal concentration (MBC) of antimicrobials, the aim of the present research was to propose impedance measurement as a valid method for the in vitro evaluation of MIC and MBC of a natural antimicrobial extract of A. platensis . To this purpose, six different concentrations of A. platensis extract (0.1%, 0.15%, 0.2%, 0.25%, 0.3% and 0.5% v/v) were tested on Pseudomonas fluorescens and Serratia liquefaciens, two species commonly involved in food spoilage, and Listeria innocua, as representative of the human food borne pathogenic species Listeria monocytogenes . The results obtained confirmed the in vitro antimicrobial potential of A. platensis extract, but also highlighted how MIC and MBC could be different depending on both the concentration of antimicrobial and the tested strain. Furthermore, the proposed method allowed the identification of MIC and MBC values in a new way never used before for this purpose. Highlights: Impedometric method for the evaluation of MIC and MBC values. A. platensis extract activity against pathogen and spoilage bacteria. MIC and MBC defined by two impedometric parameter. MIC and MBC varying depending on the strains and antimicrobic concentration.